2016
DOI: 10.1002/eji.201646405
|View full text |Cite
|
Sign up to set email alerts
|

The soluble cytoplasmic tail of CD45 (ct‐CD45) in human plasma contributes to keep T cells in a quiescent state

Abstract: The cytoplasmic tail of CD45 (ct‐CD45) is proteolytically cleaved and released upon activation of human phagocytes. It acts on T cells as an inhibitory, cytokine‐like factor in vitro. Here, we show that ct‐CD45 is abundant in human peripheral blood plasma from healthy adults compared with plasma derived from umbilical cord blood and plasma from patients with rheumatoid arthritis or systemic lupus erythematosus. Plasma depleted of ct‐CD45 enhanced T‐cell proliferation, while addition of exogenous ct‐CD45 protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 68 publications
0
27
0
Order By: Relevance
“…The mechanism of cell death involves dysregulation of Lck and inappropriate activation, leading to cell cycle arrest and ending in apoptosis/necrosis. Other studies have reported that dysregulation of CD45 using mAbs or soluble CD45 enzyme can result in cell death or lack of differentiation/ growth (Robson et al, 1996;Harashima et al, 2002;Puck et al, 2017). However, to the best of our knowledge, our study is the first to associate inhibition of CD45 activity and cell cycle arrest, a mechanism that leads to cell death.…”
Section: Discussionmentioning
confidence: 47%
“…The mechanism of cell death involves dysregulation of Lck and inappropriate activation, leading to cell cycle arrest and ending in apoptosis/necrosis. Other studies have reported that dysregulation of CD45 using mAbs or soluble CD45 enzyme can result in cell death or lack of differentiation/ growth (Robson et al, 1996;Harashima et al, 2002;Puck et al, 2017). However, to the best of our knowledge, our study is the first to associate inhibition of CD45 activity and cell cycle arrest, a mechanism that leads to cell death.…”
Section: Discussionmentioning
confidence: 47%
“…SLFN12 has previously been reported to alter the phenotype of other cells, including prostatic cancer cells [53] and activated T cells [54, 55], and to inhibit dendritic cell differentiation [11]. Slfn4, also intermediate length, regulates myelopoiesis [56].…”
Section: Discussionmentioning
confidence: 99%
“…After 3 d, cells were harvested and fixed using 70% ethanol at 4°C for 30 min. After washing, cells were stained with 50 mg/ml propidium iodide in the presence of 100 mg/ml RNAse A for 45 min at room temperature, as recently described (21). DNA content was then measured on a BD FACSCalibur Flow Cytometer and analyzed via CellQuest (BD Biosciences).…”
Section: Cell Cycle Analysismentioning
confidence: 99%
“…Supernatants were cleared from residual mAbs by overnight incubation (4°C) with Dynabeads M-280 sheep anti-mouse IgG (Thermo Fisher Scientific), followed by removal of complexes via centrifugation, as previously described (21,22). Part of the cleared supernatant was then treated with anti-IL-2 mAb clone no.…”
Section: Il-2 Depletion and Neutralization Assaymentioning
confidence: 99%